PERBEDAAN JUMLAH SEL-SEL SPERMATOSIT PRIMER DAN SPERMATID SETELAH PEMBERIAN NIKOTIN ANTARA 2 MINGGU DAN 3 MINGGU PADA MENCIT (Mus Musculus) - Iis Rahmawati* (The Indonesian Journal of Health Science, 2015)
There has been an increase in smoking habits in Indonesia and some other developing countries. The main component of cigarette is nicotine of 50% which is absorbed through the respiratory tract, mouth mucus, and skin. The effect of cigarette smoke can spoil sperm viability and spermatogenesis. It can cause hormonal condition and trigger the emergence of toxic substance on sperm that it can harm male fertility. The research design employed in this study was Post Test Only Control Group Design. The samples were adult male mus musculus. There were four groups of research subject chosen randomly after homogenization. Two groups were the control group and the other two were the experimental group. The subjects in the experimental group were injected with nicotine subcutaneously for two week, threeweeks  with the same dosage namely 5 mg/kg bodyweight/day. The final observation was aimed at calculating the number of primary sprematocyte and spermatid. The result of the  one way Anova showed that the primary spermatocyte, spermatid had a statistically significant difference on some experimental groups (p 0.05). LSD test showed that there was significant difference between spermatocyt primary cells of P3 and K3;  P2 and K3; there was significant difference between spermatid cells of P2 and K3. The conclusion of this research was that nicotine caused a decrease in the number of primary spermatocyt and spermatid.